Characterization of a novel nanocomposite film based on functionalized chitosan-Pt-Fe3O4 hybrid nanoparticles - Kumari, Sangeeta; Singh, Raj Pal; Chavan, Nayaku N.; Sahi, Shivendra V.; Sharma, Nilesh (Nanomaterials, 2021)
The development of organic-inorganic hybrids or nanocomposite films is increasingly becoming attractive in light of their emerging applications. This research focuses on the formation of a unique nanocomposite film with enhanced elasticity suitable for many biomedical applications. The physical property measurement system and transmission electron microscopy were used to analyze Pt-Fe3O4 hybrid nanoparticles. These nanohybrids exhibited magnetic effects. They were further exploited to prepare the nanocomposite films in conjunction with a chitosan-g-glycolic acid organic fraction. The nanocomposite films were then examined using standard techniques: thermogravimetric analysis, X-ray diffraction, Fourier transform infrared spectroscopy, and atomic force microscopy. Tensile strength testing demonstrated a significantly greater elastic strength of these nanocomposite films than pure chitosan films. The water absorption behavior of the nanocomposites was evaluated by measuring swelling degree. These nanocomposites were observed to have substantially improved physical properties. Such novel nanocomposites can be extended to various biomedical applications, which include drug delivery and tissue engineering.
Keywords: Chitosan; nanocomposite films; Pt-Fe3O4 hybrid nanoparticles; tensile strength testing; Thermogravimetric analysis